A time trade-off study in the UK, Canada and the US to estimate utilities associated with the treatment of haemophilia - Anna Okkels; Cecilie Yssing; Michael Lyng Wolden; Mohd Nawi Wahid (Health and Quality of Life Outcomes)
Abstract Introduction Haemophilia is a rare bleeding disorder caused by a deficient or absent clotting factor, leading to frequent bleeding. Multiple intravenous (IV) infusions have been the standard prophylactic treatment; however, newer treatment options involve less frequent subcutaneous (SC) injections. To inform future health economic evaluations, this study applied the time trade-off (TTO) method for estimation of utilities associated with haemophilia treatment for both people with the disease and potential caregivers. Methods Using the TTO method, utilities were estimated through two online surveys distributed in the UK, Canada and the US. In survey 1 (S1), adults from the general population aged 18 years and above evaluated health states as if they were living with haemophilia themselves and were receiving treatment for the condition. In survey 2 (S2), adults from the general population with a child under the age of 15 years evaluated health states as if they were treating their child for haemophilia. The surveys assessed the following treatment aspects: frequency of treatment, treatment device and injection site reactions. Results In total, 812, 739 and 703 respondents completed S1 and 712, 594 and 527 completed S2 in the UK, Canada and the US, respectively. In both surveys, the treatment device was associated with the largest impact on utilities for both people with haemophilia and caregivers. Monthly SC injections with a prefilled pen-device were associated with a significant utility gain compared with SC injections with a syringe and IV infusions. In S1, a lower treatment frequency was preferred in all three countries, while in S2, a lower treatment frequency was preferred only in the UK. Avoiding injection site reactions was associated with a significant utility gain in both surveys, but only in the UK and Canada. Conclusions The study suggests that the administration of haemophilia treatment in particular has an impact on utilities for both people and caregivers living with the disease. Thus, less complex and time-consuming treatment devices are expected to improve health-related quality of life. This can be further modified additively by less frequent administration. These results can inform future health economic analyses of haemophilia and haemophilia treatment.